17O-EPR determination of the structure and dynamics of copper single-metal sites in zeolites - Paolo Cleto Bruzzese (Nature Portfolio, 2021)
The identification of catalytically active sites with atomic-scale precision occupies a central place in the theory and practice of heterogeneous catalysis. Here the authors assess the nature of the copper-oxygen bond in a Cu-CHA zeolite and recover the microscopic structure of single-metal sites.